Analisis Bibliometrik Moderasi Beragama Dalam Pendidikan Agama Islam: analisis bibliometrik moderasi - Mardiyandi; Santiani (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
This research aims to analyze studies on religious moderation in the context of Islamic Religious Education (PAI) through bibliometric analysis. Bibliometric analysis was carried out to identify research trends, dominant topics, as well as collaboration and citation patterns in related literature. The research method used was bibliometric analysis by collecting scientific publication data from various digital sources. Data is processed and analyzed using software such as VOSviewer to visualize bibliometric maps. Publication data is collected using the publish or perish application to obtain article data in journals indexed on Google Schoolar. Received 200 articles and 137 relevant articles from the 2020-2024 time period. In 2020 from 2022 to 2024 there will be an increase and decrease in the number of articles studied from the 200 articles found. Some of these topics are often discussed in relation to religious moderation. The influence of religious moderation in Islamic religious education is very significant. And individuals who have more moderate religious views tend to be more tolerant towards individuals with different religious beliefs. keyword : Bibliometric analysis, religious moderation, PAI